Stock Prices and Inflation: A Case Study of Pakistan - Mahmood, Irum; Nazir, Fiyaz; Junid, Muhammad; Javed, Zahoor Hussain (Journal of Asian Business Strategy, 2014)
This manuscript inspects connection among inflation and stock prices in Pakistan. The observation period ranges from January, 2005 to December, 2010 have been taken from economic survey of Pakistan. The VAR is employed to locate and breakdown the friendship between dependent and independent variables. The judgment reveals that inflation is influenced negatively by pressure of stock prices. The tight monetary policy can keep the inflation at low level. Consequently investors would be certain about their returns from securities and stock prices will not be adversely affected.